A Mathematical Study on SIR Epidemic Model During COVID-19 - Meenakshi, S.; Ananthaswamy, V.; Jothi, J. Anantha; Santhi, V. K. (Communications in Mathematics and Applications, 2024)
In this study, a novel epidemic model for COVID 19 (information propagation model) which explains the dissemination of information is examined. The model is related to the total number of primary communicators, onlookers, secondary communicators, immunizers, as well as quitters at network nodes. The approximate analytical results for the five compartments represented by primary communicators, onlookers, secondary communicators, immunizers as well as quitters are obtained by employing the Homotopy analysis approach. Our approximate analytical expressions are compared with the numerical simulation (MATLAB) and are shown to be a very good fit with all parameter values. The impacts of several parameters including initial transmission rate, propagation rates, exit rate, network average degree along with quit probability are shown in the graphical representation. With the help of this technique, the epidemic models SIR (Susceptible-Infected-Recovered), SVIR (Susceptible-Vaccinated-Infected-Recovered), SEIR (Susceptible-Exposed-Infected-Recovered), SVEIR (Susceptible-Vaccinated-Exposed-Infected-Recovered) of COVID 19, malaria, tuberculosis, and HIV can be readily solved.
Keywords: SIR model; COVID-19; Non-linear initial value problem; Homotopy analysis method; Numerical simulation